PRINCIPLES OF INTERPRETATION OF A LITERARY TEXT (HOMER “THE ILIAD” BARICCO “THE ILIAD”) (Web of Teachers: Inderscience Research, 2024)
This article examines the principles of interpretation of a literary text on the example of Baricco's work “Homer. Iliad”. The definition of interpretation is given, new forms of narration, compositional features, intertextual connections in his work are considered. It is noted his ability to interpret the epic poem “Iliad”, making changes in the plot, genre, structure and style of the work. Baricco offers a modern interpretation of Homer's ancient work “Iliad”: he rewrites the text in a new style, simplifies it and adapts it for modern audience, translates Homer's war epic into prose, uses modern Italian language, adds ‘inserts’ to the narrative of the original epic.